Update on local anesthetics: focus on levobupivacaine - Burlacu, Crina L (Dove Medical Press, 2008)
In recent years levobupivacaine, the pure S (−)-enantiomer of bupivacaine, emerged as a safer alternative for regional anesthesia than its racemic parent. It demonstrated less affinity and strength of depressant effects onto myocardial and central nervous vital centers in pharmacodynamic studies, and a superior pharmacokinetic profile. Clinically, levobupivacaine is well tolerated in a variety of regional anesthesia techniques both after bolus administration and continuous postoperative infusion. Reports of toxicity with levobupivacaine are scarce and occasional toxic symptoms are usually reversible with minimal treatment with no fatal outcome. Yet, levobupivacaine has not entirely replaced bupivacaine in clinical practice. In anesthesia and analgesia practice, levobupivacaine and bupivacaine produce comparable surgical sensory block with similar adverse side effects, and equal labor pain control with comparable maternal and fetal outcome. The equipotency of the two drugs has been recently questioned, prompting clinicians to increase the dose of levobupivacaine in an attempt to ensure adequate anesthesia and analgesia and offsetting, therefore, the advantages of less motor block with levobupivacaine. In this review we aim to discuss the pharmacological essentials of the safer profile of levobupivacaine, and analyze the evidence regarding the current clinical indications.